2021
DOI: 10.3390/ijerph18147447
|View full text |Cite
|
Sign up to set email alerts
|

Guided Tissue Regeneration Treatment Yields Better Results in Class II Furcations in the Mandible Than in the Maxilla: A Retrospective Study

Abstract: Absorbable porcine collagen membrane with a bovine bone graft can be considered for regenerative treatment in periodontal class II furcation defects. We evaluated the clinical efficacy of guided tissue regeneration (GTR) treatment with bovine bone xenograft and a porcine collagen membrane in molars with class II furcations. Probing depth (PD), clinical attachment level (CAL), and bone level (BL) were recorded at baseline and at 3, 6, and 9 months postoperatively. Thirty class II furcation defects from the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The present study revealed that GTR in the mandible yielded better bone gain than in the maxilla. These outcomes are similar to those reported by Odontuya et al [ 25 ]. Other researchers explained that this difference was due to the complex morphology and accessibility of molars such as root cuvature and furcations [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that GTR in the mandible yielded better bone gain than in the maxilla. These outcomes are similar to those reported by Odontuya et al [ 25 ]. Other researchers explained that this difference was due to the complex morphology and accessibility of molars such as root cuvature and furcations [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…In 2021 Dorj, Lee et al discovered that guided tissue regeneration treatment yields to better results in severe vertical bone loss in the molar region (class II furcations) in the mandible than in the maxilla [ 15 ]. Furthermore, stem cell properties of PDLSC isolated from third molars of maxilla and mandible show intrinsic differences in proliferation and plasticity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 According to research of Dorj et al, guided tissue regeneration therapy produces better outcomes in terms of severe vertical bone loss in the mandible's molar region (class II furcations) than in the maxilla. 10 Furthermore, stem cell properties of PDLSC isolated from third molars of maxilla and mandible show intrinsic differences in proliferation and plasticity. 11 In this study, we isolated PDLSC from maxilla and mandible of the same patients and compared the angiogenic potential related to localization of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Healing may be impacted by variations between the upper versus lower jaw's odontogenic development and odontogenesis, blood supply, and innervation 9 . According to research of Dorj et al, guided tissue regeneration therapy produces better outcomes in terms of severe vertical bone loss in the mandible's molar region (class II furcations) than in the maxilla 10 . Furthermore, stem cell properties of PDLSC isolated from third molars of maxilla and mandible show intrinsic differences in proliferation and plasticity 11 …”
Section: Introductionmentioning
confidence: 99%